AN OVERVIEW OF UMTS AND WIMAX NETWORKS INTEGRATION - Wirastuti, Dewi (Majalah Ilmiah Teknologi Elektro; Vol 9, No 2 (2010): (July - December) Majalah Ilmiah Teknologi Elektro, 2012)
This paper gives an overview of the network integration of UMTS (Universal Mobile Telecommunication System) with WiMAX (Wordwide Interoperability of Microwave Access). A few proposed interworking solutions and seamless integration of both networks are explained. The best architecture and key procedures that will enable the integration both networks and handover mechanism for the seamless mobility are presented. Considering the trend of the current network evolution, which is the convergence between the telecommunications and broadcast worlds, an integration of mobile WiMAX with present 2G, 2.5G or 3G accesses into a homogeneous architecture goes a long way to achieve the reality of mobile broadband networks. With the advent of mobile WiMAX, a mobile broadband wireless access solution and based on all-IP (Internet Protocol) based OFDMA (Orthogonal Frequency Division Multiple Access) technology, an UMTS-WiMAX